2015
DOI: 10.5367/te.2014.0389
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Household Life Cycle and Tourism Expenditure in Taiwan: An Application of the Infrequency of Purchase Model

Abstract: The infrequency of purchase (IP) model was used to explore the impact of financial factors, limiting factors, social status and household life cycle on family travel intention and travel expenditure in Taiwan. The empirical results indicate that family travel intention and level of expenditure vary at different stages of the household life cycle. Additionally, family incomes, the education level of the head of the household, women's employment and home ownership have significantly positive impacts on travel in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 34 publications
4
14
0
6
Order By: Relevance
“…Hung et al (2013) pointed out that Taiwanese households with loans had lower tourism expenditure and households with vehicles had higher tourism expenditure. Sun et al (2015) also referred to data from Taiwan and found that house ownership positively affected household tourism expenditure; household healthcare expenditure, a proxy for health status, adversely influenced household tourism expenditure.…”
Section: Economic Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hung et al (2013) pointed out that Taiwanese households with loans had lower tourism expenditure and households with vehicles had higher tourism expenditure. Sun et al (2015) also referred to data from Taiwan and found that house ownership positively affected household tourism expenditure; household healthcare expenditure, a proxy for health status, adversely influenced household tourism expenditure.…”
Section: Economic Factorsmentioning
confidence: 99%
“…The gender of the head of household has received much attention as well, yet empirical findings regarding the effect of this variable on household tourism expenditure are similarly ambiguous. Zheng and Zhang (2013), Sun, Lee, and Chen (2015), and Haq et al (2019) found that the head of household's gender had no significant effect on household tourism expenditure. Fleischer and Rivlin (2009) and Zhang and Feng (2018) noted that households with male heads of household spent less per trip, while Kuo and Lu (2013) and Alegre and Pou (2016) came to the opposite conclusion.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…age, family situation, and socioeconomic status) to different travel- and leisure-related decisions—i.e. both facilitating and constraining (Backer and Lynch, 2017; Bernini and Cracolici, 2015; Choi et al, 2010; Fodness, 1992; Hong et al, 2005; Oppermann, 1995; Sun et al, 2015). According to the life cycle theory, the members of a family rationalize their decision-making process and behaviors based only on the resources available to them at the time of their decision (Bernini and Cracolici, 2015; Laszloffy, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%